Quasi Z source direct matrix converter based K- to three-phase wind energy conversion system using maximum constant boost current control modulation technique - Mani Karthick; Venkatasalam Rukkumani; Soundarapandiyan Manivannan (Automatika)
The conversion system for wind energy has no restriction on the number of output phases. K numbers of output phases can be converted into standard grid-connected three-phase supply using a quasi-Z source direct matrix converter (QZSDMC). The obtained input supply may be five phases from the wind energy conversion system with continuously variable frequency as well as variable terminal voltages. Using the proposed QZSDMC converter with maximum constant boost current control modulation technique constant three-phase voltages as well as frequency can be maintained at the grid side. Additionally, the energy conversion system has high output voltage gain. The proposed converter as well as the modulation technique produces the maximum voltage transfer ratio of 1.05. The output voltage gain reached nearly 1.99 compared with the traditional power converters. The voltage THD and current THD are maintained within the acceptable limit of 5.3 and 3.6 respectively. The power factor have been maintained nearly unity throughout the all mode of operations. To stabilize the grid frequencies and grid voltages additional control blocks are used. This research article presents simulation results for the proposed QZSDMC converter with a maximum constant boost current control modulation technique. Also, the proposed scheme has been validated with suitable experimental results.